2023
DOI: 10.3390/jcm12123909
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of Acute Bronchiolitis in Children at Risk for Asthma, with Emphasis on the Human Rhinovirus Genotyping Protocol

Abstract: This research aims to determine acute bronchiolitis’ causative virus(es) and establish a viable protocol to classify the Human Rhinovirus (HRV) species. During 2021–2022, we included children 1–24 months of age with acute bronchiolitis at risk for asthma. The nasopharyngeal samples were taken and subjected to a quantitative polymerase chain reaction (qPCR) in a viral panel. For HRV-positive samples, a high-throughput assay was applied, directing the VP4/VP2 and VP3/VP1 regions to confirm species. BLAST searchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Several studies have focused on the importance of different environmental exposure characteristics (chemicals, drugs, smoking, diet, pollution, viruses, allergens, microbiome changes) as triggers of asthma disease and its exacerbation. 8,[15][16][17][18][19][20] The current research's findings showed that most participants agreed with all of the triggers listed in the question about…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have focused on the importance of different environmental exposure characteristics (chemicals, drugs, smoking, diet, pollution, viruses, allergens, microbiome changes) as triggers of asthma disease and its exacerbation. 8,[15][16][17][18][19][20] The current research's findings showed that most participants agreed with all of the triggers listed in the question about…”
Section: Discussionmentioning
confidence: 58%
“…Results of studies carried out, such as Alsayed et al, show that human rhinovirus (HRV) is classified as the second most frequent cause of acute bronchiolitis in children at risk for asthma. In addition, these results demonstrated the potential utility of the VP4/VP2 region and the VP3/VP1 region for differentiating HRV genotypes [7].…”
Section: Viral Infections As a Risk Factor For Asthmamentioning
confidence: 71%
“…The present hospital-based study supported that HRV is the most common viral agent detected in pediatric acute LRTI cases with a prevalence of 24.1% (52/216 positive cases). Alsayed et al and Aizawa et al, in their studies, also reported HRV as the most common viral agent with different prevalence rates, 16.5% and 85.2%, respectively [ 11 , 12 ]. The difference in prevalence rates might be due to the difference in the size of the study, population, geographical location, diagnostic methods, and the period of study.…”
Section: Discussionmentioning
confidence: 99%